Interaction of Influenza A Viruses with Oviduct Explants of Different Avian Species - Sid, Hicham; Hartmann, Sandra; Winter, Christine; Rautenschlein, Silke (Frontiers in Microbiology, 2017)
Infection of poultry with low pathogenic avian influenza viruses (LPAIV) is often associated with mild respiratory symptoms but may also lead to loss in egg production in laying birds. In vivo susceptibility of the reproductive tract for LPAIV infection was reported for turkeys and chickens, but virus-interaction with epithelial cells of the oviduct and possible stimulation of the local antiviral immune responses have not been characterized. In this study, we wanted to investigate the suitability of magnum organ cultures (MOC) as an in vitro model to study virus-host interactions. We compared the susceptibility of duck (Du), chicken (Ch) and turkey (Tu) MOC for three different influenza A viruses (IAV). Overall, the course of infection and the antiviral immune response varied between strains as well as host cell origin, but the MOC cultures gave reproducible results for all investigated parameters within each species. While pandemic (p) H1N1 and H9N2 efficiently replicated in MOC-Ch and MOC-Tu, MOC-Du were significantly less susceptible to infection as indicated by a reduced replication level for both viruses (p<0.05). Overall, virus replication levels did not correlate with interferon (IFN) α mRNA-expression levels in neither species. H9N2-infection led to a significant upregulation of interferon (IFN) λ mRNA expression in MOC of all species compared to the non-infected controls (p<0.05), while a correlation with replication levels was only seen for MOC-Tu. pH1N1-infection induced only significant upregulation of IFNλ mRNA expression in MOC-Tu at 48 hours post infection (hpi) (p<0.05), but the expression pattern did not correlate with replication levels. Our results show that MOC are a suitable model to study IAV-interaction with the mucosal surface of the avian reproductive tract. The data suggest that the reproductive tract may play a role in the pathobiology of IAV in poultry.